Fabrication of feeding plate to an infant with Pierre-Robin syndrome: a case report - Challagondla, Bhargavi; Sesha Reddy, Papala; Kurakalva, Soundarya (International Journal of Dental Materials, 2021)
Cleft lip and palate is a congenital deformity associated with maxillary sagittal and transverse discrepancies. Feeding is an immediate concern in children born with a cleft as it delays their normal growth. A feeding plate is essential for proper nutrition, and it has a role in craniofacial development and decreases the incidence of otitis media and nasopharyngeal infections. This case report describes a single visit technique for fabrication of feeding prosthesis for a 5- day old new-born infant with cleft lip and palate. The prosthesis helps in reducing the flow of food into the nasopharynx, thus decreasing the incidence of Otis media and oro-nasopharyngeal infections.